Light and scanning electron microscopy of the dromedary liver with special emphasis on connective tissue fibers - Siddig, Rasha Siddig Ahmed; Abdalla, Ali Bashir (Journal of Veterinary Medicine and Animal Production, 2021)
Livers of Thirty adult dromedary camels were studied using light and scanning electron microscope (SEM) techniques. The evaluation was focused on both type and distribution of the connective tissue fibers. The present study showed that the histology of the camel liver was corresponding to that of other domestic mammals. However, some differences were observed. Well-developed connective tissue characterized the camel liver, so, the classic hepatic lobules were well delineated. The existence of a large amount of collagen fibers located in the capsule, trabeculae, portal areas and circularly-arranged around central veins were confirmed by scanning electron microscopy (SEM) examination. They appeared as abundant white wavy fibers. Thin strands of collagenous fibers extended from both trabeculae and portal areas and passed into the lobular parenchyma along the sinusoids at the perisinusoidal spaces. Unlike the situation in other mammal's liver, the hepatocyte nuclei of the camel liver were not all centrally located. A high frequency of nuclear deviation in hepatocyte sinusoidal surfaces was seen. Moreover, the hepatocyte showed numerous cytoplasmic vacuoles which may occupy most of the cell and appearing larger than the nucleus. The liver of camel, unlike that of mammals with a gallbladder, it possessed large interlobular and interlobar bile ducts which were characterized by their wide lumina and folded mucosa which producing many invaginations in the lamina propria.